The calibration for inner and outer lever-arm errors based on velocity differences of two RINSs. (November 2021) - Wu, Qi; Li, Kui; Song, Tianxiao
Highlights: The method calibrates the inner and outer lever-arm errors simultaneously by utilizing the velocity differences of two RINSs. The method designs the asynchronous rotation schemes of two RINSs distinctively and particularly. The method could achieve the autonomous calibration of inner and outer lever-arm errors in dynamic conditions. The method could enhance the linear motion information fusion accuracy of two RINSs in practical applications. Abstract: Rotational inertial navigation system (RINS) can enhance navigation accuracy by gimbals rotation. In marine applications, two or more RINSs are usually employed in the same vessel to further improve the navigation performance through information fusion. However, fusion accuracy of linear motion information is influenced by the lever-arm effect errors caused by the inner lever-arm errors between the accelerometers and axes of rotation of RINS and the outer lever-arm errors between two RINSs, which should be accurately calibrated and compensated for high-precision applications. In this paper, the calibration method for inner and outer lever-arm errors of two RINSs is proposed. The method only utilizes the navigation information of two RINSs instead of external reference information to realize the calibration of the inner and outer lever-arm errors of two RINSs. The lever-arm models are deduced, and the asynchronous rotation schemes are designed by the characteristics of lever-arm errors of two RINSs. Then Kalman filter with velocity differences of two RINSs as measurements is constructed to estimate all inner and outer lever-arm errors. The method is adequately verified by simulations and experiments. Results indicate that the inner and outer lever-arm errors could be accurately calibrated and the standard deviations of calibration results are less than 1 mm. The oscillations of velocity differences of two RINSs could be obviously restrained and even disappear after the compensation of calibration results, which demonstrates the effectiveness of the proposed calibration method.